2017
DOI: 10.1139/bcb-2016-0050
|View full text |Cite
|
Sign up to set email alerts
|

Aerosolized bovine lactoferrin reduces neutrophils and pro-inflammatory cytokines in mouse models of Pseudomonas aeruginosa lung infections

Abstract: Lactoferrin (Lf), an iron-chelating glycoprotein of innate immunity, produced by exocrine glands and neutrophils in infection/inflammation sites, is one of the most abundant defence molecules in airway secretions. Lf, a pleiotropic molecule, exhibits antibacterial and anti-inflammatory functions. These properties may play a relevant role in airway infections characterized by exaggerated inflammatory response, as in Pseudomonas aeruginosa lung infection in cystic fibrosis (CF) subjects. To verify the Lf role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 47 publications
(41 reference statements)
2
42
0
Order By: Relevance
“…This effect could mask the beneficial antibacterial activity of the molecule. Microaerosol administration, or alternative devices, could be considered for further assays (Valenti et al, 2017). As a further strategy to decrease the D -BMAP18 cytotoxicity, is now under investigation its administration as a cleavable pro-drug, in order to guarantee a controlled release of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…This effect could mask the beneficial antibacterial activity of the molecule. Microaerosol administration, or alternative devices, could be considered for further assays (Valenti et al, 2017). As a further strategy to decrease the D -BMAP18 cytotoxicity, is now under investigation its administration as a cleavable pro-drug, in order to guarantee a controlled release of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Non-invasive administration routes remain preferable in humans and among them, although bearing some limitations, oral management represents a safe and practical approach for Lf supplementation. Beside oral administration [48], several different other modes have been tested in animal models and humans, including aerosolized [45,46], intranasal [52], sublingual [53], intravenous [54], intraperitoneal [55], and intravaginal administration [56].…”
Section: Lactoferrin Bioavailability: Absorption and Body Deliverymentioning
confidence: 99%
“…Despite the structural differences reported above, bLf has been classified as and hLf bioequivalent by virtue of high sequence homology and function sharing and, in addition, it is classified as a "generally recognized as safe" (GRAS) substance by the USA Food and Drug Administration. Therefore, the majority of the in vitro [43,44] and in vivo studies [45,46], as well as clinical trials [47,48] have been conducted by using commercial bLf rather than the highly costing rhLf. Furthermore, bLf is currently used to supplement food products and cosmetics, to inhibit oxidation due to its iron-binding capacity, and in infant formulas to improve the immune response in newborn.…”
mentioning
confidence: 99%
“…This consequently means that its bacteriostatic effect can prevent biofilm development, but also disrupt cells which have already become adherent. Lactoferrin has the additional benefit of exhibiting anti-inflammatory properties, which may play an important role in mitigating chronic inflammation associated with delayed wound healing (Valenti et al, 2017). Allison et al (2015) showed that as a component of breast milk, lactoferrin at a concentration of 3 mg ml À1 significantly decreased Streptococcus mutans biofilm formation in vitro.…”
Section: Current Treatment Strategies For Biofilms In Chronic Woundsmentioning
confidence: 99%